2014
DOI: 10.2478/s11772-014-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in UV emission and band gap by Fe doping in ZnO thin films

Abstract: Enhancement of the optical band gap of ZnO from 3.14 to 3.29 eV has been obtained using Fe dopant. Undoped and doped ZnO films are deposited by sol-gel spin coating. XRD patterns indicate polycrystalline nature and hexagonal wurtzite structure of Zn1−xFexO films. EDX analysis confirms the presence of iron dopant. The photoluminescence spectra show an ultraviolet emission peak at 398 nm (NBE emission) and defect emission peak at 485 nm. Intensity of the NBE emission is much higher for the doped samples with its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…2. All the films have a hexagonal wurtzite structure with major diffraction peaks along (1 0 0), (0 0 2) and (1 0 1) planes [1,3,16,21]. No impurity peak relating to iron is found.…”
Section: X-ray Diffractionmentioning
confidence: 89%
See 3 more Smart Citations
“…2. All the films have a hexagonal wurtzite structure with major diffraction peaks along (1 0 0), (0 0 2) and (1 0 1) planes [1,3,16,21]. No impurity peak relating to iron is found.…”
Section: X-ray Diffractionmentioning
confidence: 89%
“…In [12], the films were deposited by spray pyrolysis and the decrease in optical band gap was attributed to s-d and p-d hybridization. Previously, Srivastava et al [1] reported an increment in optical band gap in Fe doped ZnO films of a thickness 500 nm obtained by sol-gel spin coating using precursor solutions of the molarity of 0.1 M. It was concluded that sp hybridization is responsible for this behavior. Other reports in the literature regarding the increase in the band gap of Fe doped ZnO with an increase in dopant concentration, explained it by Burstein Moss effect [13] and quantum confinement [14].…”
Section: Uv-vis Spectra and Optical Band Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe doped ZnO films have been prepared by variety of preparation methods such as DC thermal plasma [7], RF magnetron sputtering [8,9], spray pyrolysis [10], chemical co-precipitation [11] and sol-gel [12,13]. Compared with other methods, the sol-gel offers the greatest possibility for depositing a film with large area at low cost for applications.…”
Section: Introductionmentioning
confidence: 99%